2020
DOI: 10.1002/ece3.6878
|View full text |Cite
|
Sign up to set email alerts
|

Investigating life‐history traits of Steller sea lions with multistate hidden Markov mark–recapture models: Age at weaning and body size effects

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 112 publications
1
31
0
Order By: Relevance
“…With this study, we aimed to explore variation in age‐ and sex‐specific vital rates to improve ecological understanding that can inform future management and recovery actions under the Endangered Species Act. In general, survival rates estimated in this study for the eastern portion of the wDPS range were similar to (or higher than) previous estimates (Fritz et al, 2014; Maniscalco et al, 2015; Pendleton et al, 2006; York, 1994) and those estimated for the eastern distinct population segment (DPS) (Hastings et al, 2011, 2021; Wright et al, 2017). However, survival rates for the western portion of the wDPS range (western and central Aleutian Islands) estimated here for the first time are notably lower than those in the eastern portion of the range, particularly for male pups, yearlings of both sexes, and juvenile females aged 2–5.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With this study, we aimed to explore variation in age‐ and sex‐specific vital rates to improve ecological understanding that can inform future management and recovery actions under the Endangered Species Act. In general, survival rates estimated in this study for the eastern portion of the wDPS range were similar to (or higher than) previous estimates (Fritz et al, 2014; Maniscalco et al, 2015; Pendleton et al, 2006; York, 1994) and those estimated for the eastern distinct population segment (DPS) (Hastings et al, 2011, 2021; Wright et al, 2017). However, survival rates for the western portion of the wDPS range (western and central Aleutian Islands) estimated here for the first time are notably lower than those in the eastern portion of the range, particularly for male pups, yearlings of both sexes, and juvenile females aged 2–5.…”
Section: Discussionsupporting
confidence: 89%
“…However, females can compensate for smaller pup size by increasing maternal investment and/or weaning later (Lee et al, 1991; Trillmich, 1990), providing support for the assertion that maternal care influences first‐year survival more than birth mass for otariids (Boyd, 1990; McMahon & Hindell, 2003). Hastings et al (2021) found that in certain rookeries in both the eastern and western DPSs, earlier weaned yearlings had a lower probability of survival and that heavier pups were more likely to wean by one year of age. Applying these concepts to our findings, it is possible that the larger pups in the western portion of the range incur a larger burden on lactating females (as was found in South American sea lions, Otaria flavescens , who foraged longer for heavier pups; Drago et al, 2021) and may habitually be weaned sooner and therefore ultimately experience lower survival rates despite their larger size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resighting surveys of marked animals occurred at all rookeries and major haulouts in Southeast Alaska during dedicated large-scale boat-based surveys and one field camp each summer from 2002 to 2019 (Hastings et al, 2011;Pendleton et al, 2006) Few Steller sea lion females (1.9%-3.7%) can have both a dependent juvenile and pup during the pupping season (aka "triad"), in which case most often the juvenile is favored over the new pup by the end of the pupping season (Hastings et al, 2021;Maniscalco & Parker, 2009). Of 211 females With-Juvenile*year, only four (1.9%) were also observed with a pup during the survey window, and for these four cases, the pup data were replaced with the juvenile sightings.…”
Section: Field Data Collectionmentioning
confidence: 99%
“…juvenile survival in the north, compared to population stability, large population size, smaller neonates, lower juvenile survival, higher survival cost of weaning for juveniles, and more extensive animal movements in the south, where the population is considered near carrying capacity (Hastings et al, 2011(Hastings et al, , 2021Jemison et al, 2018;Mathews et al, 2011;Pitcher et al, 2007). Therefore, regional differences in reproductive output may indicate female response to variation in environmental productivity and/or local abundance.…”
Section: T a X O N O M Y C L A S S I F I C A T I O Nmentioning
confidence: 99%